Automatic semi-quantification of [123I]FP-CIT SPECT scans in healthy volunteers using BasGan version 2: results from the ENC-DAT database - Nobili, Flavio; Naseri, Mehrdad; De Carli, Fabrizio; Asenbaum, Susan; Booij, Jan; Darcourt, Jacques; Ell, Peter; Kapucu, Özlem; Kemp, Paul; Varer, Claus; Morbelli, Silvia; Pagani, Marco; et al. (European journal of nuclear medicine and molecular imaging, 2013)
Purpose The aim of this study was to assess striatal dopamine transporter (DAT) availability in a large group of normal subjects. Methods The study included 122 healthy subjects, aged 18–83 years, recruited in the multicentre ‘ENC-DAT’ study (promoted by the European Association of Nuclear Medicine). Brain single photon emission computed tomography (SPECT) was acquired by means of dual-head cameras 3 h after [ 123 I]FP-CIT administration. Specific to nondisplaceable binding ratios (SBRs) in the basal ganglia were computed using the ‘BasGan’ software, allowing automatic value extraction with partial volume effect correction. Multicentre camera inhomogeneity was taken into account by calibrating values on basal ganglia phantom data. SBR in each caudate nucleus (C) and putamen (P) were the dependent variables in a repeated measures general linear model analysis; age, gender, handedness and body mass index (BMI) were the independent variables. Results SBR values in C and P were significantly associated with age (mean rate decrease with age: 0.0306 per year, or 0.57 % of the general mean; p < 0.0001) and gender (women had higher values; p = 0.015), while no significant effect was found for handedness and BMI. A significant interaction was found between age and region ( p < 0.0001) as the age-related decline was 0.028 for left C, 0.026 for right C and 0.034 for both P. P/C ratio analysis confirmed that age-related SBR decrease was stronger in P than in C ( p < 0.0001). No significant effect was found for season or time of the day when the scan was acquired by analysing the residual of SBR values in C and P, after subtraction of age and gender effects. Conclusion This study confirms the dependency of DAT on ageing and highlights the gender differences in a large sample of healthy subjects, while it does not support the dependency of DAT on BMI, handedness, circadian rhythm or season.